Extraction Of Naphthenic Acid From Indonesian Crude Oils By Methanol-Ammonium Solution - Anda Lucia (Testing Center for Oil and Gas LEMIGAS, 2011)
Indonesia’s crude oil which has a total acid number (TAN) with a concentration more than 0.5 mg KOH/g are often found. The presence of naphtenic acid tends to increase the value of TAN. The existence of naphthenic acid needs to be reduced to avoid problems in the petroleum refining process because it will cause problems of corrosion, foaming, etc. On the other hand, naphthenic acid may have a value-added as an emulsifier, antiseptics timber, preservatives, and so on. This study extracted naphthenic acid from some Indonesian crude oils which have relatively high TAN value oil with the code A, B and C. Extraction of naphthenic acid from crude B shows quite high results of that is equal to 65.47% with a purity level of 96.6%